Scaling the Security Staircase. Issue 4 (4th December 2020) - Carr, Stuart C.; Hopner, Veronica; Hakim, Moh. Abdul; Hodgetts, Darrin J.; Chamberlain, Kerry; Nelson, Nicholas; Ball, Rhys; Jones, Harvey
Abstract : Building on the U.N. human security taxonomy of 1994, this article aims to explore the constructability of a reliable, valid, parsimonious, useful measure of human security that is relevant to contemporary environments and situations? A seminal 1994 U.N. report, Human Security in Theory and Practice, outlined seven types of human security (personal, health, food, community, economic, environmental, political). A quarter‐century on, we added two more, cyber and national security, and tested if a single measure could capture all nine security concerns. A national sample of N  = 1033 New Zealanders completed a brief online measure in which participants reported yes or no to experiencing each type of security and basic demographics. Guttman scaling placed these needs in an ascending order of difficulty. Analogous to a staircase, security may be scaled from personal up to political security (coefficient of reproducibility = .88), with three distinct but interrelated flights: (1) proximal (personal, health, food security); (2) social (cyber, community, economic, environmental); and (3) distal (national, political). We confirmed this nine‐step, three‐flight measure in our sample ( Χ 2  = 81.72; df  = 24; RMSEA = .048, 90%CI [.037, .06]; CFI = .976; TLI = .964; SRMR = .028). The measure showed configural, metric, scalar, and factorial invariances (across random‐split subgroups). Ethnic groups and the precariously employed scored significantly differently, in coherent ways, on the security staircase scale .